Refinement Method of Retaining Wall (L-Shape Concrete) and CCSP Design in Kalimas Quayside Kademeter 1200-1400 Project - Margantionius Margantionius; Ronny Durrotun Nasihien (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
As one of the state-owned enterprises (BUMN), PT Pelabuhan Indonesia III (Persero) Regional Jawa Timur has demanded to obtain the considerable revenues using the limited maintenance funds for port facilities. One of the roles of Engineering Division includes the availability of port facilities that support operation division, so it is necessary to check and maintain the facilities. In consequence, the estimated cost and time of project carried out effectively to mitigate the risk level in the future in order to achieve the main objectives. One of the biggest revenues in the port sector is on the quayside facility services, therefore, maintenance of these facilities needs to be prioritized. The final project provides an analysis of cost and time calculations using the method of repairing the retaining wall (L-Shape Concrete) and the CCSP (Coruggated Concrete Sheet Pile) method for repairing damage to Kalimas Kademeter Quayside 1200-1400 with damage length of 176 meters and width of 9 meters. Based on the observation of cost and time analysis, the estimated cost of using the L-Shape Concrete repair method is much cheaper than using the CCSP (Coruggated Concrete Sheet Pile) method, but the actual project period is much longer. Finally, the selection of repair methods can adjust to the necessity of cost and time aspects, as well as the methods of project.